Gendered Language and Power: A Critical Discourse Analysis of Men’s Interpretation in Skincare Beauty Ads Featuring Korean Male Actors through Lakoff’s Linguistic Framework - Anastasia Datam Dendo; Isti'anatul Hikmah (Universitas Sarjanawiyata Tamansiswa, 2025)
This research investigates the relationship between the use of women's language and therepresentation of Korean male actors in skincare advertisements. It also explored publicperceptions of this representation. The research aims to examine (a) the linguisticfeatures associated with Lakoff’s theory of womens language appear in selected skincarebeauty advertisements starring Korean male actors and (b) the linguistic featuresinfluence on gender stereotypes.This study uses a qualitative descriptive method, with digital audio-visual material,specifically transcripts of five selected advertisement starring Korean male actors, as wellas structured interview results. The researcher uses Lakoff's (1975) Women's Languagetheory analyze women's language in advertisements, Fairclough's (1995) CDA theory andHall's (1997) representation theory to analyze the meaning of male representation in skincare products.Based on the result, the researcher found 3 women’s languages used, namely emptyadjectives, intensifiers and emphatic stress. Furthermore, this representation has a significantimpact on the public, by raising awareness of self-care among men, then as a naturalizationprocess that encourages the transition to modern masculinity, and the creation of new beautystandards with Korean male actors as role models. Keyword: Advertisement, CDA, gender stereotypes, representation